Experimental and Numerical Modeling of Screws Used for Rigid Internal Fixation of Mandibular Fractures. (15th May 2008) - Chaudhary, Naresh; Lovald, Scott T.; Wagner, Jon; Khraishi, Tariq; Baack, Bret
Abstract : Experimental and numerical methods are used to explore the stresses generated around bone screws used in rigid internal fixation of mandibular fractures. These results are intended to aid in decisions concerning both the design and the use of these bone screws. A finite element (FE) model of a human mandible is created with a fixated fracture in the parasymphyseal region. The mandibular model is anatomically loaded, and the forces exerted by the fixation plate onto the simplified screws are obtained and transferred to another finite element submodel of a screw implant embedded in a trilaminate block with material properties of cortical and cancellous bone. The stress in the bone surrounding the screw implant is obtained and compared for different screw configurations. The submodel analyses are further compared to and validated with simple axial experimental and numerical screw pull-out models. Results of the screw FE analysis (FEA) submodel show that a unicortical screw of 2.6 mm major diameter and 1.0 mm pitch will cause less bone damage than a bicortical screw of 2.3 mm major diameter and 1.0 mm pitch. The results of this study suggest that bicortical drilling can be avoided by using screws of a larger major diameter.